Rediscovering Paul : an Introduction to His World, Letters, and Theology. - Capes, David B. (InterVarsity Press, 2017)
For some of us, the apostle Paul is intimidating, prickly, and unpredictable. But maybe it's time to get to know Paul on his own terms. Drawing on the best of contemporary scholarship, and with language shaped by conversations with today's students, this expanded edition of Rediscovering Paul gives fresh consideration to Paul's conversion, call, and his ongoing impact on church and culture.